Situation Report: Baltic Area, 25 September 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. What the Writers' Union Congress Really Talked About / by Toomas Ilves Homeless Derelicts / by Toomas Ilves Soviet Latvian Press on Chernobyl: A Whitewash of the Estonian Report / by Dzintra Bungs Aggressive Soviet View of US Baltic Policy / by Dzintra Bungs New Party Secretaries (NEW) / by Dzintra Bungs New Lutheran Archbishop / by Dzintra Bungs Lithuanians on the Admiral Nakhimov / by Saulius Girnius